2016
DOI: 10.2528/pierc16042806
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Tunable Ferrite-Dielectric Left-Handed Metamaterial

Abstract: Abstract-In this paper, a magnetically tunable metamaterial is proposed and studied. The metamaterial is based on the combination of ferrite sheets and dielectric rods. The tunable property is originated from the ferromagnetic resonance and electric response of dielectric rods. The retrieved electromagnetic parameters and transmission characteristic showed that by simultaneously inspiring the ferromagnetic resonance and electric resonance, composite metamaterial can possess double-negative band in the resonant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…In 2016, Yang et al demonstrated a "ring-shaped" 5 × 5-mm 2 meta-atom for wearable, flexible and stretchable microwave meta-skin, with clocking effects from 8-13 GHz and an effective medium ratio of six [5]. In 2016, Du et al presented a left-handed metamaterial created by the combination of ferrite sheets and dielectric rods to investigate the electromagnetic properties for X-band applications [20]. In 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Yang et al demonstrated a "ring-shaped" 5 × 5-mm 2 meta-atom for wearable, flexible and stretchable microwave meta-skin, with clocking effects from 8-13 GHz and an effective medium ratio of six [5]. In 2016, Du et al presented a left-handed metamaterial created by the combination of ferrite sheets and dielectric rods to investigate the electromagnetic properties for X-band applications [20]. In 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions of the designed meta-atom are 10 × 10 mm 2 , which is compact in size according to the effective medium ratio and comparison with [5,17,19,[21][22][23]. The proposed meta-atom unit cell and arrays also exhibit more frequency bands with a wider bandwidth than [1, 4,5,16,17,[19][20][21][22][23]. Moreover, the proposed meta-atom is used for enhancing the antenna bandwidth, number of frequency bands and gain because the number of frequency bands, bandwidth and gain of the antenna can be improved by using the partial or slotted or fractal or meta-atom integrated ground plane.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Holloway proposed a structure using dielectric particles embedded into a dielectric background material to produce negative permittivity and permeability, based on Mie resonance. Since then, several all‐dielectric structures, which can behave as left‐handed or negative index metamaterials, have been proposed. These dielectric metamaterials (DMM) require a high permittivity cube or particle as the resonating unit cell, leading to limited flexibility and increased fabrication complexity, particularly in the high‐frequency operating band.…”
Section: Introductionmentioning
confidence: 99%
“…There are various strategies reported for tuning the magnetic resonance of the permeability include electrical control [16,17], magnetically control [18], and temperature changing [19,20]. Generally, tunability is introduced by ferromagnetic materials [21,22], ferroelectric [13,23], liquid crystal [20,24,25], etc. However, the abovementioned tunable NIMs mostly operated at the low frequencies or high losses.…”
Section: Introductionmentioning
confidence: 99%